Esophagoplasty with a presternal peristaltic gastric tube: about three observations - Gilardoni, Federico; Moller, Germán; Capandeguy, Enrique; Pollak, Erik; Filgueira, José; Pereyra Borrelli, César (Cirugía del Uruguay, 2020)
The paper presents the result of observations in three patients suffering from cancer of the esophagus. An artificial esophagus was made utilizing a subcutaneous peristaltic gastric tube. One of the patients died a month after the operation, and two survive. One is under treatment due to a fistulous relapse in the neck and 'ecent metastasis; the other patient, is clínica] well two years later, with good functional result of the gastric tube. The observations on the vascularization of gastric tubes and the length and ascent achieved, is presented. An important suture defect was observed in the inmediate postoperatory period, involving anastomotic tension and distension of the gastric tube, but did not require decompressive gastrostomy. There is a repeated tendency to fistulization of the anastomosis due to the ramming effect of swallowing in the "Angle Area"; this however, is susceptible of repair as can be seen in the case of the first patient. lt is for this reason that au artificial esophagus with stomach should not be utilized as a first choice in a patiente in colon esophageal resection is possible. The presternal peristaltic gastric tube, due to the limitations in the ascent, should not be employed in thecase of high esophageal lesions when the esophagostoma is located high we in the neck. The obtention of a large tube should be considered in the first period, in cases when gastrostomy is to be performed in the highest possible location. The procedure should be limited to cancers of the middle esophagus so as to maintain a proximal stomach and feeding gastrostomy which protects the cervical esophagogastr.c anastomosis. For this same reason, in the case of a small stomach where the is difficulty in leaving an upper gastric sector with its gastrostomy, another method of esophagoplastia should be employed. These cases form part of an inicial series, and we believe that as we acquire experience we shall be able to eliminate sone of the mentioned problems.